Improving Emotional and Spiritual Intelligence of Students through Aqidah Morals - Moh Kamaluddin; Adawiyah Adawiyah; Rusdin Rusdin (Department of Islamic Education, Postgraduate Program State Institute for Islamic Studies Palu, 2020)
The aim of this paper is to discusses Improving Emotional and Spiritual Intelligence of Students through Aqidah Morals. This study uses qualitative methods and data was gathered through observation, in-depth interviews, and written material. Data analysis was analyzed using grounded theory approach. The results showed that the teacher's efforts in improving discipline, honesty, responsibility, and cooperation of students at Madrasah Aliyah 2 Palu City through learning Akidah Akhlak were carried out by providing exemplary in terms of punctual arrival in class, advice and motivation, sanctions/punishment, making students' friends as assisting teachers, applying the discussion method in learning.